A process model for usability and maintainability design reviews. (2nd November 2018) - Liu, Yifan; Messner, John I.; Leicht, Robert M.
ABSTRACT: Most of the previous research on design reviews focuses on management and technology innovations that improve the effectiveness of design reviews. To better evaluate the impact of those innovations, a structured view of the design review process is needed, but few previous works have provided such a view. This research studies the dynamics of usability and maintainability design review meetings that involve stakeholders in the post-occupancy phase of the building, including owners, occupants, and facility operators. The outcomes of the research include a process model, which describes the communication and interaction dynamics between the participants in those design reviews. The process model is developed and validated following grounded theory methodology through analyzing 20.5 h of the video recordings from 13 design review meetings, which are from real projects with diverse sizes and types. The process model defines the core of the design review process as three cycles of activities, which are called Understand, Validate, and Resolve Cycle respectively. The process model also defines the interactions among activity cycles and how they advance the design review process. This research contributes to the fundamental theory of design review process and provides a roadmap for other researchers to analyze the usability and maintainability design reviews. To further support future researchers' evaluation of design review process, we also proposed a theory to derive the design review meeting performance by analyzing the time spent in each activity cycles. This theory can be used as a foundation by future researchers to evaluate and compare the impact of technology and process innovations on design reviews meetings.